Degradation evaluation by distribution of relaxation times analysis for microtubular solid oxide fuel cells. (10th April 2020) - Sumi, Hirofumi; Shimada, Hiroyuki; Yamaguchi, Yuki; Yamaguchi, Toshiaki; Fujishiro, Yoshinobu
Abstract: Distribution of relaxation times (DRT) analysis is a powerful assistant tool for electrochemical impedance spectroscopy (EIS) deconvolution. In the present work, electrode degradation is evaluated by estimation of polarization resistances using DRT analysis. Five or six DRT peaks are detected for anode-supported microtubular solid oxide fuel cells (SOFCs) at 600–650 °C. In a reduction-oxidation (redox) cycling test, the polarization resistance of charge transfer and ionic conduction processes in the anode increases due to the decrease in triple phase boundary (TPB) length. On the other hand, initial electrode degradation is also successfully evaluated using DRT analysis during a galvanostatic test. The rapid growth of nickel grains in the anode and the relatively slow growth of La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) grains in the cathode are observed after the test, which corresponds with the increase in the polarization resistance of charge transfer and ionic conduction processes in the anode and that of oxygen surface exchange and diffusion processes in the cathode, respectively.